A Big Data Approach to Assessing the Impact of Social Norms: Reporting One’s Exercise to a Social Media Audience - Carpenter, Christopher J. and Amaravadi, Chandra S. (Communication Research, 2019)
Assessing the impact of an individual’s social network on an individual is difficult without administering a large number of surveys. Online social networks with built-in data collection circumvent this problem. The data collected by an exercise-focused social media website and mobile app allowed the estimation of the effect of both the behavior of the social network and the size of that network on the behavior of individual service users (31,200 users reporting 67,699 exercise events with a potential range of 87 weeks). The results are consistent with the theory of normative social behavior in that the amount of exercise reported by the user’s social network as well as the size of the user’s on-site social network affected the user’s exercise behavior over time.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMDkzNjUwMjE2NjU3Nzc2